Inorganic Materials Confined in Carbon and Boron Nitride Nanotubes - Cull, William J. (2024)
The use of carbon nanotubes (CNTs) for the encapsulation of chemical species and the formation of functional nanocomposite materials has been well documented. Conversely, the utilisation of boron nitride nanotubes (BNNTs) for the same purpose has remained relatively understudied. The work presented in this thesis investigates the effect of the chemical composition of the encapsulating nanotube (NT) on both the properties of the resultant nanocomposite material and the ability to probe the chemical and physical state of the encapsulated species. Synthetic methods to produce a variety of CNT and BNNT based nanocomposite materials are reported, alongside rigorous analysis of these materials by aberration-corrected transmission electron microscopy (AC-TEM) and a variety of other spectroscopic and analytical methods.